Current Mechanistic Concepts in Ischemia and Reperfusion Injury - Wu, Meng-Yu; Yiang, Giou-Teng; Liao, Wan-Ting; Tsai, Andy Po-Yi; Cheng, Yeung-Leung; Cheng, Pei-Wen; Li, Chia-Ying; Li, Chia-Jung (Cellular physiology and biochemistry, 2018)
Ischemia-reperfusion injury is associated with serious clinical manifestations, including myocardial hibernation, acute heart failure, cerebral dysfunction, gastrointestinal dysfunction, systemic inflammatory response syndrome, and multiple organ dysfunction syndrome. Ischemia-reperfusion injury is a critical medical condition that poses an important therapeutic challenge for physicians. In this review article, we present recent advances focusing on the basic pathophysiology of ischemia-reperfusion injury, especially the involvement of reactive oxygen species and cell death pathways. The involvement of the NADPH oxidase system, nitric oxide synthase system, and xanthine oxidase system are also described. When the blood supply is re-established after prolonged ischemia, local inflammation and ROS production increase, leading to secondary injury. Cell damage induced by prolonged ischemia-reperfusion injury may lead to apoptosis, autophagy, necrosis, and necroptosis. We highlight the latest mechanistic insights into reperfusion-injury-induced cell death via these different processes. The interlinked signaling pathways of cell death could offer new targets for therapeutic approaches. Treatment approaches for ischemia-reperfusion injury are also reviewed. We believe that understanding the pathophysiology ischemia-reperfusion injury will enable the development of novel treatment interventions.